Functional Evaluation of Proteins in Watery and Gel Saliva of Aphids - van Bel, Aart J. E.; Will, Torsten (Frontiers in Plant Science, 2016)
Abstract Gel and watery saliva are regarded as key players in aphid-pIant interactions. The salivary composition seems to be influenced by the variable environment encountered by the stylet tip. Milieu sensing has been postulated to provide information needed for proper stylet navigation and for the required switches between gel and watery saliva secretion during stylet progress. Both the chemical and physical factors involved in sensing of the stylet’s environment are discussed. To investigate the salivary proteome, proteins were collected from dissected gland extracts or artificial diets in a range of studies. We discuss the advantages and disadvantages of either collection method. Several proteins were identified by functional assays or by use of proteomic tools, while most of their functions still remain unknown. These studies disclosed the presence of at least two proteins carrying numerous sulfhydryl groups that may act as the sheath backbone. Furthermore, cell-wall degrading proteins such a pectinases, pectin methylesterases, polygalacturonases, and cellulases as well as diverse Ca2+-binding proteins (e.g. regucalcin, ARMET proteins) were detected. Suppression of the plant defence may be a common goal of salivary proteins. Salivary proteases are likely involved in the breakdown of sieve-element proteins to invalidate plant defence or to increase the availability of organic N compounds. Salivary polyphenoloxidases, peroxidases and oxidoreductases were suggested to detoxify e.g. plant phenols. During the last years, an increasing number of salivary proteins have been categorized under the term ‘effector’. Effectors may act in the suppression (C002 or MIF cytokine) or the induction (e.g. Mp10 or Mp 42) of plant defence, respectively. A remarkable component of watery saliva seems the protein GroEL that originates from Buchnera aphidicola, the obligate symbiont of aphids and probably reflects an excretory product that induces plant defence responses. Furthermore, chitin fragments in the saliva may trigger defence reactions (e.g. callose deposition). The functions of identified proteins and protein classes are discussed with regard to physical and chemical characteristics of apoplasmic and symplasmic plant compartments.